α-hemihydrate calcium sulfate/octacalcium phosphate combined with sodium hyaluronate promotes bone marrow-derived mesenchymal stem cell osteogenesis in vitro and in vivo - Chen C; Zhu C; Hu X; Yu Q; Zheng Q; Tao S; Fan L (Dove Medical Press, 2018)
Changshun Chen,1 Chen Zhu,2 Xiang Hu,1 Qiuli Yu,3 Qianjin Zheng,1 Shengxiang Tao,1 Lihong Fan2 1Department of Orthopedics, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, China; 2School of Chemistry, Chemical Engineering and Life Sciences, Wuhan University of Technology, Wuhan, Hubei, China; 3School of Health Sciences, Wuhan University, Wuhan, Hubei, China Purpose: The aims of this research were to combine a-hemihydrate calcium sulfate/octacalcium phosphate (α-CSH/OCP) with sodium hyaluronate (SH) or SH sulfate (SHS) to determine whether these composites can be used as a new type of bone repair material. This study may provide a theoretical basis and new ideas for the construction of active bone repair materials and their clinical application.Methods: In this study, we combined α-CSH/OCP with SH or SHS. Scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis (TGA), and the wettability test were performed, and porosity, setting time, in vitro degradation, and the mechanical properties of these composite materials were analyzed to evaluate the ultrastructural and physicochemical properties. We evaluated the histocompatibility of these composites by MTT assay, hemolysis, acute toxicity, and pyrogenic and intracutaneous stimulation tests. In addition, the osteogenic differentiation ability of these materials was detected in vitro using Western blot analysis and in vivo using an animal model of bone defect.Results: The α-CSH/OCP/SH composite had a compressive strength of 13.72 MPa, a porous rate of 27.45%, and the 28-day degradation rate of 64%. The MTT assay results showed that the relative proliferation rates of the α-CSH/OCP/SH group were greater than 90%. The results of the α-CSH/OCP/SH composite in the hemolysis, acute toxicity, pyrogenic, and intracutaneous stimulation tests were within the normal range. Western blot analysis indicated that the expression of bone extracellular matrix (ECM) proteins was notably upregulated and always higher in the α-CSH/OCP/SH group than in the other groups. XRD of the rabbit radius-defect model indicated that bone healing in the area implanted with α-CSH/OCP/SH was excellent approximately 9 weeks after repair.Conclusion: α-CSH/OCP/SH has very good biocompatibility and exhibits clear advantages in the induction of bone regeneration and self-repair, and this compound shows promise in the field of bone tissue engineering. Keywords: sodium hyaluronate, characterization, BMSCs, biocompatibility, osteogenic differentiation